Study of endemic species at the territory of Karkaraly rayon of Karagandy region - Бакеев, Р.Т.; Атикеева, С.Н. (Fundamental and Experimental Biology, 2015)
As result of analysis of Central Kazakhstan flora the growing of 34 species of endemic plants were conducted at the the territory of Karkaraly rayon of Karagandy region. It is 5 % from common species amount of endems of Kazakhstan. The living forms and basic growing conditions were determined.